Korelasi Kadar Gula Darah Sewaktu (GDS) Dengan Jumlah Trombosit Pada Pasien Diabetes Mellitus Tipe 2 Di Rumah Sakit Dr.H Bob Bazar SKM Lampung Selatan - Rina Kriswiastiny; Zulfian Zulfian; Deviani Utami; Fristy Dhea Laorenzi (Universitas Malahayati, 2022)
ABSTRACT Chronic hyperglycemia and insulin resistance in people with type 2 diabetes mellitus cause vascular damage that begins with endothelial dysfunction due to the process of glycosylation and oxidative stress in endothelial cells, where endothelial dysfunction is a condition where the endothelial loses its physiological function such as increasing vasodilation, fibrinolysis, and anti-platelet aggregation. The endothelial layer plays a role in facilitating physical barriers between blood vessel walls and the lumen, by secreting a number of mediators to regulate platelet aggregation, coagulation and fibrinolysis. To determine the relationship between the time blood sugar levels value and the platelet count in type 2 Diabetes mellitus patients at Hospital DR.H. Bob Bazar South Lampung. This research design is correlative analytic with cross sectional method using purposive sampling as many as 201 samples of type 2 Diabetes mellitus patients who match with the inculsion criteria. Data collecting begin in January 2021. The data on this research used secondary data in the form of medical records. After the dat collected, data will evaluated by the Spearman test. The research sample was 201 patients with type 2 diabetes with a minimum value of the time blood sugar levels levels contained in the data 120 mg / dl, the maximum value of the time blood sugar levels levels found in the data was 392 mg / dl and the average time blood sugar level was 227 mg / dl, for the number of platelets. obtained the maximum value of the number of platelets contained in the data is 556,000, the minimum value of the number of platelets in the data is 110,000 and the mean value of platelet count is 266,363. The results of the Spearman correlation showed that the value of p = 0.071 and the value of r = 0.128, because the value of p = 0.071> 0.05 so that it can be stated that Ha is rejected and Ho is accepted or there is no relationship between the two variables studied, with r = 0.128 which means there is no relationship or a weak correlation between time blood sugar levels and platelet counts in type 2 Diabetes mellitus patients at DR. H. Bob Bazar, SKM Hospital South Lampung. There is no relationship between time blood sugar levels and platelet counts in type 2 Diabetes Mellitus patients at DR.H. Bob Bazar, SKM Hospital South Lampung in 2020 with results of p = 0.071 and r = 0.128. Keywords: Diabetes Mellitus, Time Blood Sugar Levels , Platelet ABSTRAK Hiperglikemia kronik dan resistensi insulin pada penderita DM tipe 2 meyebabkan kerusakan vaskuler yang diawali dengan terjadinya disfungsi endotel akibat proses glikosilasi dan stres oksidatif pada sel endotel, dimana disfungsi endotel merupakan kondisi endotel kehilangan fungsi fisiologisnya seperti meningkatkan vasodilatasi, fibrinolysis, dan anti agregasi trombosit. Lapisan endotel berperan untuk memfasilitasi hambatan fisik antara dinding pembuluh darah dengan lumen, dengan cara menysekresikan sejumlah mediator guna mengatur agregasi trombosit, koagulasi dan fibrinolysis. Tujuan penelitian ini untuk mengetahui hubungan antara nilai GDS dengan jumlah trombosit pada pasien DM tipe 2 di Rumah Sakit DR.H. Bob Bazar Lampung Selatan. Jenis Penelitian ini adalah analitik korelatif dengan metode cross sectional menggunakan purposive sampling sebanyak 201 sampel pasien DM tipe 2 yang memenuhi kriteria inkulsi. Pengambilan data dimulai pada bulan Januari 2021. Data yang digunakan yaitu data sekunder berupa rekam medik. Data dievaluasi dengan uji Spearman. Didapatkan sampel penelitian berjumlah 201 pasien DM tipe 2 dengan nilai minimal dari Kadar GDS yang terdapat di data 120 mg/dl , nilai maksimal dari kadar GDS yang terdapat di data 392 mg/dl dan rerata Kadar GDS yaitu 227 mg/dl, untuk jumlah trombosit didapatkan nilai maksimal Jumlah trombosit yang terdapat di data yaitu 556.000 , nilai minimal Jumlah trombosit yang terdapat di data 110.000 dan nilai rerata Jumlah trombosit adalah 266.363. hasil korelasi Spearman didapatkan nilai p=0,071 dan nilai r=0,128, karena nilai p=0,071 > 0,05 sehingga dapat dinyatakan Ha ditolak dan Ho diterima atau tidak terdapat hubungan antara kedua variabel yang diteliti, dengan r=0,128 dapat diartikan tidak terdapat hubungan atau berhubungan lemah antara kadar GDS dengan jumlah trombosit pada pasien DM tipe 2 di Rumah Sakit DR. H. Bob Bazar, SKM Lampung Selatan. Tidak terdapat hubungan antara kadar GDS dengan jumlah trombosit pada pasien DM tipe 2 di Rumah Sakit DR.H. Bob Bazar, SKM Lampung Selatan tahun 2020 dengan hasil p=0,071 dan r=0,128. Kata Kunci: Diabetes Mellitus, Kadar GDS, Jumlah Trombosit